Betta mahachaiensis, a new species of bubble-nesting fighting fish (Teleostei: Osphronemidae) from Samut Sakhon Province, Thailand - Kowasupat, Chanon; Panijpan, Bhinyo; Ruenwongsa, Pintip; Sriwattanarothai, Namkang (Zootaxa, 2012)
Betta mahachaiensis, a new species of fighting fish belonging to the Betta splendens group, is described. The fish inhabitsspecifically sites with brackish water and nipa palms in the Samut Sakhon Province, Thailand. It is distinguishable from othermembers of the B. splendens group in having an iridescent green/bluish-green appearance on the brown-to-black bodybackground. The opercular membrane has brown-to-black colour without red streaks or patches. The opercle has two paralleliridescent green or bluish-green vertical bars. Its dorsal, caudal, and anal fin rays are brown to black, contrasting with theiridescent green or bluish-green of the interradial membrane. Black transverse bars are present on at least the proximal two-thirds of the dorsal fin, but not on the caudal fin. The colour of the pelvic fins is brown to black with an iridescent green/ bluish-green front margin and a white tip. Females possess similar characters but are less colourful than males.